Comparative Analysis of Concrete Compressive Strength Using GGBFS as a Cement Substitute for Normal Concrete - Achmad Trie Mashuri; Ahmad Yudi; Ayu Sinta Aprilia (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Building constructions found in Indonesia generally use concrete as the main structural material. This research aims to analyze the use of ground granulated blast furnace slag (GGBFS) as a cement substitute in concrete mixtures using the Analysis of Variance method (Anova) and the Tukey Method. The GGBFS levels used are 0%, 25%, 30%, 35%, 40% and 45% as cement substitute. The average compressive strength values ​​obtained for each sample were 25.08 MPa, 25.1 MPa, 25.7 MPa, 25.9 MPa, 26.4 MPa, 27.7 MPa and 26.2 respectively. MPa. The compressive strength value continues to increase with the highest compressive strength value at 40% and decreasing again at 45%. The use of ggbfs requires an activator to accelerate the mechanical properties of ggbfs itself. The activator used is NaOH with a concentration of 4 Mol.